Sliding mode control with directly learned feedforward compensation - Xu, Jian-Xin; Song, Yanbin (Zielona Góra: Uniwersytet Zielonogórski)
A new control method synthesizing direct learning control (DLC) with sliding mode control (SMC) is proposed for the tracking problem of a class of non-linear high order systems. Sliding mode control is used to provide the control system with indispensable robustness in the presence of strong system uncertainties. A new learning control method, the direct learning control method, is developed and used to generate the desired feedforward compensation for SMC.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka